Peningkatan Mutu Fisiologis Benih Padi Lokal Jambi melalui Invigorasi: Peningkatan Mutu Fisiologis Benih Padi Lokal Jambi melalui Invigorasi - Suci Primilestari; Eva Salvia; Ambar Yuswi Perdani (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2019)
Seed decline is a certain occurrence. Local rice variety planting by farmers generally uses seeds from the previous crop and has been stored for a long time before being replanted. This study aimed to determine the optimal hydropriming invigoration material in improving the physiological quality of some Jambi local rice varieties. The treatment was applied to factorial complete randomized design with 3 replications. 1st factor was rice varieties: Padi Karya, Kuning Betung, Kuning Kerinci, and Gadis Jambi. 2nd factor was invigoration consisting of control (aqua dest), red onion solution and a solution of young coconut water. A total of 30 seeds for each experimental unit were soaked for 24 hours. Seeds were planted on moist filter paper media according to a test method on paper. Results showed that there were no significant interactions between varieties and invigoration on the germination of local rice seeds tested. The invigoration treatment using coconut water significantly affected root length, plumula length, normal sprout length, and local rice vigor index. Kuning Betung variety provides the best response to invigoration. Invigoration treatment is an effort to improve seed performance to reduce the risk of failure on field plantation, expected to have the implications for increasing rice production.